Payment and settlement system development in Nepal: hurdles and way out - Giri, Pralhad (Economic Journal of Development Issues, 2015)
As stipulated in Nepal Rastra Bank Act, 2002 under article 4 (C), one of the prime objectives of the central bank is to develop a secure, healthy and efficient system of payment, where the function of the same has been given in Article 5 (i) as to establish and promote the system of payment, clearing and settlement and to regulate these activities. Advent of new payment gateway backed by technology has prompted Nepal to develop an efficient national payment system to regulate all the electronic payment mechanism in the country and help integrate small businesses and consumers in the economy. This paper is an attempt of deriving the assessment of payment system of Nepal, with a view to modernize its scope for smooth functioning of financial system. The study suggests that central bank should act on promulgating solid legal and regulatory framework by establishing separate Payment and Settlement Division in order to carry out the function of oversight and operations. It is further recommended to harmonize relations with different government authorities to liberalize infrastructure services; thus ensures smooth execution different payment and settlement services.DOI: http://dx.doi.org/10.3126/ejdi.v15i1-2.11871Economic Journal of Development Issues Vol. 15 & 16 No. 1-2, pp. 116-127